Christmas at the Island Hotel [large type] : a novel - Colgan, Jenny (Harper Large Print, an imprint of HarperCollins Publishers, 2020)
On the remote island of Mure, a new hotel opening is a big event. New mother Flora MacKenzie and her brother Fintan are working themselves half to death to get it ready in time for Christmas. The new hotel's impressive kitchens throw together two unlikely new friends: Isla Gregor is the hardworking young girl who has been a waitress in the island's cafe, dreaming of a bigger, better life now that she's at a proper fancy hotel. Konstantin Pederson is working his way up in the hotel's kitchens too, but he is also, secretly, the only son of the Duke of Utsire. Konstantin has been sent to learn what it is to work hard for a living, before receiving his inheritance. Although he's initially resentful, the place grows on him; he has never met anyone quite like Isla and her fellow Murians before. As the island's residents and special VIP guests gather for the hotel's grand opening gala, Christmas is in the air. But so are more than a few small-town secrets.